FUNGSI TARI SABEK’N APA’K SEBAGAI RITUAL DALAM UPACARA NYOBENG SUKU DAYAK BINA’EH KABUPATEN BENGKAYANG - Marsianus Roji; Winda Istiandini; Ismunandar Ismunandar (Universitas Tanjungpura, 2019)
Abstract This research was backgrounded by the researcher’s great curiosity towards thefunction of Sabek’n Apa'k as a ritual in the Nyobeng ceremony of the Bina'ehDayak Tribe in Tamong Village, Siding District. The objective of this study was todescribe the process of the Nyobeng ritual ceremony as well as the function ofSabek’k Apa’k dance as the part of the Nyobeng ritual ceremony of the Bina’eh. The method used in this research was descriptive method in the form of qualitativeresearch. The data collected from observation, interviews, and documentation wereanalyzed qualitatively with the speakers Mr. Musen, Mr. Jono, and Mr. Tagongwho knew clearly about the Sabek'n Apa’k dance of the Bina’eh Dayak tribe. Basedon data analysis, it was found that the Sabek'n Apa'k dance functions as animportant ritual of Nyobeng and plays an important role for the Bina'eh. AndSabek'n Apa'k must be preceded by a ritual using offerings such as chicken, palmwine, sticky rice, eggs, hanjuang leaves, bananas, taro, Ganeng, tobacco, yellowrice. The results of this study are expected to contribute to education, presentedthrough learning media such as PowerPoint presentation and video of Sabek'nApa'k dance as teaching material in schools.Keywords: Nyobeng, Ritual, Sabek’n Apa’k dance